Pancreatic β cell interleukin-22 receptor subunit alpha 1 deficiency impairs β cell function in type 2 diabetes via cytochrome b5 reductase 3 - Fan Yu; Shuting Xie; Tongyu Wang; Yeping Huang; Hong Zhang; Danfeng Peng; Yifan Feng; Yumei Yang; Zheyu Zhang; Yunxia Zhu; Zhuoxian Meng; Rong Zhang; et al. (Cell Reports)
Summary: Impaired β cell function is a hallmark of type 2 diabetes (T2D), but the underlying cellular signaling machineries that regulate β cell function remain unknown. Here, we identify that the interleukin-22 receptor subunit alpha 1 (IL-22RA1), known as a co-receptor for IL-22, is downregulated in human and mouse T2D β cells. Mice with β cell Il22ra1 knockout (Il22ra1βKO) exhibit defective insulin secretion and impaired glucose tolerance after being fed a high-fat diet (HFD) or an HFD/low dose of streptozotocin (STZ). Mechanistically, β cell IL-22RA1 deficiency inhibits cytochrome b5 reductase 3 (CYB5R3) expression via the IL-22RA1/signal transducer and activator of the transcription 3 (STAT3)/c-Jun axis, thereby impairing mitochondrial function and reducing β cell identity. Overexpression of CYB5R3 reinstates mitochondrial function, β cell identity, and insulin secretion in Il22ra1βKO mice. Moreover, the pharmacological activation of CYB5R3 with tetrahydroindenoindole restores insulin secretion in Il22ra1βKO mice, IL-22RA1-knockdown human islets, and Min6 cells. In conclusion, these findings suggest an important role of IL-22RA1 in preserving β cell function in T2D, which offers a potential therapeutic target for treating diabetes.